2005
DOI: 10.1143/jjap.44.715
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cu2ZnSnS4 Thin Films Prepared by Photo-Chemical Deposition

Abstract: Cu2ZnSnS4 thin films were prepared by photo-chemical deposition (PCD) from aqueous solution containing CuSO4, ZnSO4, SnSO4 and Na2S2O3. The compositional ratio of the films was dependent little on pH of aqueous solution and the surface of the samples became smooth by use of aqueous filter. A sample annealed at 400°C was a p-type semiconductor and showed photoconductivity. This is the first observation of photo-conductivity from semiconductor films deposited by PCD, to the best of our knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 5 publications
0
24
0
Order By: Relevance
“…In order to reduce the cost of producing CZTS thin films, it is necessary to use a non-vacuum process. Several research groups have fabricated CZTS thin films using a spray technique [4], photochemical deposition [5], electrodeposition [6,7] and a sol-gel method [8,9]. We have reported the fabrication and characterization of CZTS thin films by sulfurizing sequential electroplated precursors (Cu/Sn/Zn stacked layers) [10,11].…”
mentioning
confidence: 99%
“…In order to reduce the cost of producing CZTS thin films, it is necessary to use a non-vacuum process. Several research groups have fabricated CZTS thin films using a spray technique [4], photochemical deposition [5], electrodeposition [6,7] and a sol-gel method [8,9]. We have reported the fabrication and characterization of CZTS thin films by sulfurizing sequential electroplated precursors (Cu/Sn/Zn stacked layers) [10,11].…”
mentioning
confidence: 99%
“…The surface morphology of films with added dextrin was composed of uniformly sized grains. Furthermore, the surfaces became smoother with increasing amounts of added dextrin [28,29]. From the above, it seems that metal complexes are formed by the addition of dextrin [32].…”
Section: Contributedmentioning
confidence: 84%
“…We also revealed that the chemical composition of the films was dependent on the solution pH [28]. Unfortunately, the surface morphology of the CZTS films prepared by PCD was rough [28,29].…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Moriya et al prepared CZTS thin films by photo-chemical deposition (PCD) and observed photoconductivity for the first time in CZTS films prepared by PCD [8]. Araki et al prepared CZTS thin films by sulfurizing electronplated precursors [9].…”
mentioning
confidence: 99%